2013
DOI: 10.1080/09712119.2013.792736
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of the synchrony programmes in subestrus crossbred cows at smallholder farms in Bangladesh

Abstract: The objective was to compare the reproductive efficacy of a Cosynch (GnRH-PGF 2a ( GnRH 'TAI), PG programme (one shot PGF 2a ) with artificial insemination (AI) on observed estrus and untreated control (AI on observed estrus) in subestrus (cycling but not detected in estrus by ]60 days postpartum) crossbred cows at smallholder farms. Ultrasonographic examinations were performed at AI, 7 d after AI and 28 d and 42 d after AI to determine the largest follicle, the new corpus luteum (CL) and to diagnose conceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The result supports the report of Shamsuddin et al (2001) and Haque et al (2015), who found 54.3% -57.9% pregnancy rate. The pregnancy rate is higher than the findings of Kamal et al (2013); Mahmoud et al (2013) but lower than those of Howlader et al (2019) and Khatun et al (2014). The factors affecting the pregnancy rate of inseminated cows are depicted in Table 7.…”
Section: Resultsmentioning
confidence: 52%
“…The result supports the report of Shamsuddin et al (2001) and Haque et al (2015), who found 54.3% -57.9% pregnancy rate. The pregnancy rate is higher than the findings of Kamal et al (2013); Mahmoud et al (2013) but lower than those of Howlader et al (2019) and Khatun et al (2014). The factors affecting the pregnancy rate of inseminated cows are depicted in Table 7.…”
Section: Resultsmentioning
confidence: 52%
“…Second, emergency unawareness means the condition of being unaware or uninformed regarding the occurrence of an emergency (Kamal et al 2013). Various alternatives may be performed in the field, but those are not directly related to the issue of emergency or its management.…”
Section: Literature Reviewmentioning
confidence: 99%